Cancer immunotherapies: A hope for the uncurable? - Hamdan, Firas; Cerullo, Vincenzo (Frontiers in Molecular Medicine, 2023)
The use of cancer immunotherapies is not novel but has been used over the decades in the clinic. Only recently have we found the true potential of stimulating an anti-tumor response after the breakthrough of checkpoint inhibitors. Cancer immunotherapies have become the first line treatment for many malignancies at various stages. Nevertheless, the clinical results in terms of overall survival and progression free survival were not as anticipated. Majority of cancer patients do not respond to immunotherapies and the reasons differ. Hence, further improvements for cancer immunotherapies are crucially needed. In the review, we will discuss various forms of cancer immunotherapies that are being tested or already in the clinic. Moreover, we also highlight future directions to improve such therapies.